2013
DOI: 10.3762/bjoc.9.283
|View full text |Cite
|
Sign up to set email alerts
|

Triol-promoted activation of C–F bonds: Amination of benzylic fluorides under highly concentrated conditions mediated by 1,1,1-tris(hydroxymethyl)propane

Abstract: SummaryActivation of the C–F bond of benzylic fluorides was achieved using 1,1,1-tris(hydroxymethyl)propane (2) as a hydrogen bond-donating agent. Investigations demonstrated that hydrogen bond-donating solvents are promoting the activation and hydrogen bond-accepting ones are hindering it. However, the reaction is best run under highly concentrated conditions, where solvents cannot interfere with the interaction between the organofluorine compound and the triol. Various benzylic fluorides react with secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…At low activator loadings, the catalyst gets quickly ''poisoned'' by the fluorides and could therefore be unable to coordinate and activate the benzylic fluorine. 3 In conclusion, the nucleophilic substitution of a benzylic fluoride by morpholine promoted by alcohols has been studied Water was the only solvent that would enhance the reactivity of our substrate, as expected from our previous work [11,12]. However, competing experiments demonstrated that at 100 8C, water is a better activator than the triol itself and most of the observed conversion was due to water.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…At low activator loadings, the catalyst gets quickly ''poisoned'' by the fluorides and could therefore be unable to coordinate and activate the benzylic fluorine. 3 In conclusion, the nucleophilic substitution of a benzylic fluoride by morpholine promoted by alcohols has been studied Water was the only solvent that would enhance the reactivity of our substrate, as expected from our previous work [11,12]. However, competing experiments demonstrated that at 100 8C, water is a better activator than the triol itself and most of the observed conversion was due to water.…”
Section: Resultsmentioning
confidence: 49%
“…This can be seen by both the length of the H-bonds and the F-H-O angles ( Table 1). In contrast, the H-bonds in the dicoordinated transition structure (TS 2H-bonds ) are reminiscent of the length and angles observed for the strong H-bonds with water, described in the previous study [11]. The relative free energies of both transition structures show that the stronger 2 H-bonds found in TS 2H-bonds offer an overall better acceleration of the S N 2 process than the 3 weaker H-bonds of TS 3H-bonds .…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations